1998
DOI: 10.1159/000055468
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the ‘Fines’ Hypothesis of Primary Open-Angle Glaucoma: The Possible Role of Alpha-Crystallin

Abstract: Primary open-angle glaucoma is a disease caused by an increase in intraocular pressure due to a decreased facility of outflow of aqueous humor through the trabecular meshwork. The etiology of primary open-angle glaucoma is currently unknown, but it has been suggested that one possible mechanism may be the obstruction of flow through the trabecular meshwork by small macromolecules, analogous to the effect of ‘fines’ in column chromatography. One such candidate is α-crystallin, a lens protein which may be releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Primary open-angle glaucoma is a disease mainly caused by an increase in intraocular pressure due to a decreased facility of out¯ow of aqueous humour through the trabecular meshwork. The etiology of POAG is currently unknown, but it has been suggested that one possible mechanism may be the obstruction of¯ow through the trabecular meshwork by macromolecules (Doss, Ward and Koretz, 1998). Studies have identi®ed several forms of glutathione S-transferases belonging to the three major enzyme classes (Alpha, Mu and Pi) in iris, ciliary body and lens (Ahmad et al, 1989;Huang et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Primary open-angle glaucoma is a disease mainly caused by an increase in intraocular pressure due to a decreased facility of out¯ow of aqueous humour through the trabecular meshwork. The etiology of POAG is currently unknown, but it has been suggested that one possible mechanism may be the obstruction of¯ow through the trabecular meshwork by macromolecules (Doss, Ward and Koretz, 1998). Studies have identi®ed several forms of glutathione S-transferases belonging to the three major enzyme classes (Alpha, Mu and Pi) in iris, ciliary body and lens (Ahmad et al, 1989;Huang et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Following up on the initial report of Johnson, et al (1993), other investigators began to explore whether smaller plasma-derived proteins (termed “fines”) might contribute to normal aqueous outflow resistance (Doss, Ward and Koretz, 1998; Russell, Koretz and Epstein, 1993). While this work provided general support for the possibility that certain proteins could influence outflow resistance, additional work on the role of proteins being added to the aqueous humor just prior to the outflow pathway is warranted.…”
Section: Potential Ramifications Of This New Modelmentioning
confidence: 99%
“…In this context, it must be emphasised that the cellular consequences of heat and ischemia are similar. Albumin, the major aqueous humor protein, acts as a escort through the trabecular meshwork in mammalian eyes, and interacts with alpha-crystallin up to the critical micelle concentration for alpha-crystallin (3.5-5 mg/ml or 0.18-0.25 mM) as reported by Doss et al [29]. There is little in-teraction at or above this concentration.…”
Section: Discussionmentioning
confidence: 86%